Aufklärung und Hofkultur in Dresden

[Art.] 651 ›Monumenta Paderbornensia‹ - Süßmann, Johannes (Credo. Christianisierung Europas im Mittelalter. Eine Ausstellung im Erzbischöflichen Diözesanmuseum, im Museum in der Kaiserpfalz und in der Städtischen Galerie Am Abdinghof zu Paderborn, 26. Juli bis 3. November 2013, Bd. 2: Katalog)

mm-Wave System-On-Chip Design in 0,13µm SiGe BiCMOS - Scheytt, Christoph; Sun, Yaoming; Schmalz, Klaus; Mao, Yanfei; Wang, Ruoyu; Debski, Wojciech; Winkler, Wolfgang (W 06 (EuMC & EuMIC))

Design and Analysis of Down-Conversion Gate/Base-Pumped Harmonic Mixers Using Novel Reduced-Size 180 ^° Hybrid With Different Input Frequencies - Kuo, Jhe-Jia; Lien, Chun-Hsien; Tsai, Zuo-Min; Lin, Kun-You; Schmalz, Klaus; Scheytt, Christoph; Wang, Huei (Microwave Theory and Techniques, IEEE Transactions on)
In this paper, a novel 180°hybrid with different input frequencies is proposed to combine RF and local oscillator (LO) signals with different frequencies in a gate/base-pumped harmonic mixer. The detailed analysis and design procedures are presented in this paper. To further reduce the chip size, the multilayer metallization above the lossy silicon substrate is employed to implement the hybrid. A V-band down-converted 2× harmonic mixer in 90-nm CMOS process and a D-band down-converted 4× harmonic mixer in the 130-nm SiGe process are designed, fabricated, and measured to verify the concept. The 2× harmonic mixer possesses 0-dB conversion gain at 60 GHz with 0-dBm LO power with merely 2.4-mW dc power. The 4× harmonic mixer achieves 0.5-dB conversion gain at 120 GHz with 2-dBm LO power and 27.3-mW dc power. With the proposed reduced-size 180° hybrid, gate/base-pumped harmonic mixers are very attractive in transceivers demanding low LO frequency and power.

Nano-/Mikroelektronik als Enabler für neue Ansätze - Scheytt, Christoph (HNI-Forum September)
50 Jahre Moore‘s Gesetz ? „More Moore“ & „More than Moore“ ? Miniatur-Radar-System ? Silizium-Photonik für schnelle Kommunikation ? Photonischer Winkelsensor

RF-MST Cluster Workshop on MEMSWAVE 2013 - Scheytt, Christoph (RF-MST Cluster Workshop on MEMSWAVE 2013)

Strategies for Energy-Efficient 100 Gb/s Baseband - Scheytt, Christoph; Kraemer, Rolf; Kallfass, Ingmar (W 19 (EuMC & EuMIC))

A 220-245 GHz Switched Beam Butler Matrix in 0,13µm SiGe BiCMOS technology - Elkhouly, Mohamed; Mao, Yanfei; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (IEEE BIPOLAR / BiCMOS CIRCUITS AND TECHNOLOGY MEETING,)
This paper presents a 220-245 GHz 4 way Butler Matrix chip in 0.13μm SiGe BiCMOS technology. The chip features four 230 GHz amplifiers with almost 9 dB of gain. A SP4T switch is integrated to select between the four outputs of the beamforming network. Finally, an amplifier used to compensate the losses of the SP4T is integrated. The chip exhibits 0 dB of insertion gain and draws 104 mA from 3.3 V supply mainly consumed by the amplifiers. The entire chip occupies 1.5 × 2.4 mm 2 .

Fighting the Financial Crisis in Greece: The Privileged Company to Protect Production and Trade in Currants (1905) as International Bank Cooperation - Schönhärl, Korinna (The Historical Review/La Revue Historique)
The global economic crisis in the 1890s affected the economy of Greece severely, and in 1893 the Greek State had to stop servicing its foreign debt. Part of the problem was the lack of diversity of Greek agricultural production, which was focused on raisins and currants (especially flavourful raisins, grown exclusively in the area around Corinth) for export. The collapse of market prices for this good seriously affected the Greek treasury and society in the growing regions. The Greek government responded by trying to withhold part of the harvest in fertile years to stabilise world market prices. Plans to organise a monopoly company for the currant trade necessitated high sums of capital from abroad. This article investigates the question of how foreign bankers in London (Hambro & Son, Emile Erlanger) and Paris (Banque de l’Union Parisienne) could be convinced to participate in the project. Which factors allowed foreign bankers to trust in the Greek national economy despite its poor reputation? What factors influenced their risk management? The focus is on the role of Greek brokers in persuading the foreigners to invest in Greece, especially the role played by Ioannis Pesmazoglou, the director of the young and innovative Bank of Athens.
Keywords: History

122 GHz Patch Antenna Designs by Using BCB Above SiGe BiCMOS wafer process for system-on-chip applications - Wang, Ruoyu; Kaynak, Mehmet; Sun, Yaoming; Borngräber, Johannes; Beer, Stefan; Goettel, B.; Scheytt, Christoph (24th Annual IEEE International Symposium on Personal, Indoor and Mobile Radio Communications)
Two half-wavelength 122 GHz patch antennas were designed and manufactured by using Benzocyclobutene (BCB) as a dielectric layer above the SiGe BiCMOS wafer. It enables the full integration of the millimeter-wave transceiver circuits and the antennas on a single chip to simplify the packaging procedure at millimeter-wave frequencies, thereby reducing the cost. The two patch antennas are fed by different feeding methods, i.e. microstrip transmission line direct feed and proximity-coupled feed. They exhibit similar performance and offer the flexibility of designing the interconnects (feed lines routing) between the circuits and the antennas within the very limited chip area. The measured gain is 3.4 dBi at 122.5 GHz (the center frequency of the ISM band of 122-123 GHz) for both designs with a simulated efficiency of about 50%.

The Economies of Urban Diversity. The Ruhr Area and Istanbul
The Economics of Urban Diversity explores ethnic and religious minorities in urban economies. In this exciting work, the contributors develop an integrative approach to urban diversity and economy by employing concepts from different studies and linking historical and contemporary analyses of economic, societal, demographic, and cultural development. Contributors from a variety of disciplines geography, economics, history, sociology, anthropology, and planning make for a transdisciplinary analysis of past and present migration-related economic and social issues, which helps to better understand the situation of ethnic and religious minorities in metropolitan areas today.

Zur Qualität professioneller pädagogischer Diagnostik im Schulalltag. Forschungsbefunde und -desiderate - van Ophuysen, Stefanie; Lintorf, Katrin; Bloh, Bea (Schul- und Bildungsforschung. Diskussionen, Befunde und Perspektiven.)

Wirkungszusammenhänge innerschulischer Kooperation: Lehrer-Lehrer-Kooperation und multiprofessionelle Kooperation an Ganz- und Halbtagsschulen - Bloh, Bea

Book review: Christoph Schubert (2009). 'Raumkonstitution durch Sprache: Blickführung, Bildschemata und Kohäsion in Deskriptionssequenzen englischer Texte.' Tübingen: Max Niemeyer - Mildorf, Jarmila (Informationsmittel für Bibliotheken)

Referential Frameworks and Focalization in a Craft Artist’s Life Story: A Socionarratological Perspective on Narrative Identity - Mildorf, Jarmila (Rethinking Narrative Identity: Persona and Perspective)

'Unnatural’ Narratives? The Case of Second-Person Narration - Mildorf, Jarmila (The Travelling Concepts of Narrative)

Teaching Medical Students about Medical Ethics and Domestic Violence: Alice Munro’s Short Story ‘Dimensions.’ - Mildorf, Jarmila (The Writing Cure: Literature and Medicine in Context)

The Writing Cure: Literature and Medicine in Context - Mildorf, Jarmila; Lembert-Heidenreich, Alexandra (The Writing Cure: Literature and Medicine in Context)

Studying Writing in Second Person: A Response to Joshua Parker - Mildorf, Jarmila (Connotations: Journal for Critical Debate)

Reading Fictional Dialogue: Reflections on a Cognitive-Pragmatic Reception Theory - Mildorf, Jarmila (Anglistik)

Warum Geld für Hellas? Die Verschuldung Griechenlands in den 1880er Jahren - Schönhärl, Korinna (Bankenhistorisches Archiv)

Themenheft: Die Börse als Ort von Ressourcenkonflikten im 19. und 20. Jahrhundert (Bankhistorisches Archiv)

The Economies of Urban Diversity: An Introduction - Reuschke, Darja; Salzbrunn, Monika; Schönhärl, Korinna (The Economies of Urban Diversity)
As European Capitals of Culture in 2010 and metropolitan areas of immigration and transmigration, both Istanbul and the Ruhr Area (Essen was designated as European Capital of Culture on behalf of the Ruhr Area) share a complex cultural and social history. Strong human, political, and economic ties have long linked the European Capital of Culture of Turkey to Germany’s main immigration region, which is about to become a new cultural center thanks to the recognition of its industrial heritage by UNESCO (Zeche Zollverein in Essen).1 Even though the cultural history of each region is different, a crisscross reading of ‘parallel lives’ between the two countries helps to understand better the use and the potential of urban diversity over time

The Writing Cure: Literature and Medicine in Context

A 125-GHz Permittivity Sensor With Read-Out Circuit in a 250-nm SiGe BiCMOS Technology - Laemmle, Benjamin; Schmalz, Klaus; Scheytt, Christoph; Weigel, Robert; Kissinger, Dietmar (Microwave Theory and Techniques, IEEE Transactions on)
In this paper, an integrated dielectric sensor with a read-out circuit in an unmodified SiGe BiCMOS technology at 125 GHz is presented. The sensor consists of a 500-μm shorted half-wave coplanar-waveguide transmission line in the uppermost metal layer of the silicon process, while the read-out is obtained by reflection coefficient measurement with an integrated reflectometer and a signal source. The reflectometer is verified with a circuit breakout including an integrated dummy sensor. The reflectometer is able to measure the phase of the reflection coefficient from 117 to 134 GHz with a resolution of 0.1° and a standard deviation of 0.082°. The integrated sensor with the reflectometer circuit have been fabricated in a 190-GHz fT SiGe:C BiCMOS technology. It spans an area of 1.4 mm 2 and consumes 75 mA from a 3.3-V supply. The circuit has been assembled on a printed circuit board for characterization by immersion into test liquids. The sensor is controlled by a controller board and a personal computer enabling a measurement time of up to 1 ms per frequency point. Functionality of the sensor is demonstrated from 118 to 133 GHz with immersion of the sensor into different binary methanol-ethanol mixtures, showing good correlation between theory and measurement. The sensor shows a standard deviation of the measured phase of 0.220° and is able to detect a difference in ε' r of 0.0125

„Urbanität“ in Zeiten der Krise: Der Basler Arbeitsrappen - Schönhärl, Korinna (Neue Städte für einen neuen Staat. Die städtebauliche Erfindung des modernen Israel und der Wiederaufbau in der BRD. Eine Annäherung)

Neue Ansätze für miniaturisierte, hochintegrierte Abstands-, Geschwindigkeits- und Drehwinkelsensoren - Scheytt, Christoph; Grau, Günter (Wissenschaftsforum 2013, Intelligente Technische Systeme, Heinz Nixdorf Institut)

Introduction to Integrated mm‐Wave Sensors - Scheytt, Christoph (System, IC and Integrated Antenna Design for Miniaturized, Millimeter-wave Radar Sensors)

220–250-GHz Phased-Array Circuits in 0.13- μ\hbox m SiGe BiCMOS Technology - Elkhouly, Mohamed; Glisic, Srdjan; Meliani, Chafik; Ellinger, Frank; Scheytt, Christoph (Microwave Theory and Techniques, IEEE Transactions on)
This paper describes the design of D-band phased-array circuits in 0.25 μm technology. The first part describes the design of the passive components which are used in the phased-array systems such as balun, Wilkinson divider and branch-line coupler. A millimeter-wave vector-modulator is designed to support both amplitude and phase control for beam-forming applications. In the second part the designed circuits are integrated together to form a two channel 110-130 GHz phased-array chip. Each channel exhibits 360° phase control with 15 dB of amplitude control range and gain of -10 dB. The entire chip draws 45 mA from 3.3 V supply. The millimeter-wave phase shifting and the low-power consumption makes it ideal for highly integrated scalable beam-forming systems for both imaging and communication.

Analysis and minimization of substrate spurs in fractional-N frequency synthesizers - Osmany, Sabbir Ahmed; Herzel, Frank; Scheytt, Christoph (Analog Integrated Circuits and Signal Processing)
This paper analyses substrate-related spurious tones in fractional-N phase- locked loops with integrated VCOs. Spur positions are calculated and experimentally verified as a function of the divider ratios of prescaler and programmable divider. For an integrated wideband PLL in SiGe BiCMOS technology the spur power levels are measured and compared with theoretical expectations. The power in these spurs is minimized by layout techniques shielding the reference input buffer. Spur minimization by using a variable reference frequency is experimentally demonstrated. Based on this observation, a programmable integer-N PLL for driving the fractional-N synthesizer is suggested to reduce the worst-case spur level significantly. Index Terms — Fractional-N, frequency synthesizers, fractional spurs, substrate spurs, phase-locked loops (PLLs), phase noise.

Flip-Chip Package with Integrated Antenna on a Polyimide Substrate for a 122-GHz Bistatic Radar IC - Beer, Stefan; Girma, Mekdes Gebresilassie; Sun, Yaoming; Winkler, Wolfgang; Debski, Wojciech; Paaso, Jaska; Kunkel, Gerhard; Scheytt, Christoph; Hasch, Jürgen; Zwick, Thomas (7th EUROPEAN CONFERENCE ON ANTENNAS AND PROPAGATION)
This paper presents the packaging technology and the integrated antenna design for a miniaturized 122-GHz radar sensor. The package layout and the assembly process are shortly explained. Measurements of the antenna including the flip chip interconnect are presented that have been achieved by replacing the IC with a dummy chip that only contains a through-line. Afterwards, radiation pattern measurements are shown that were recorded using the radar sensor as transmitter. Finally, details of the fully integrated radar sensor are given, together with results of the first Doppler measurements.

Mentoring für Lehramtstudierende- ‚Politische, partizipative Bildung in der Lehrerausbildung? - Helle, J.; Stroot, T.; Treidler, M.; Westphal, Petra (Deutsche Vereinigung für politische Bildung - NW e.V.: Politisches Lernen)

Computing time investigations for variational multirate integration - Gail, T.; Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Set oriented methods for the numerical treatment of multi-objective optimization problems - Schütze, O.; Witting, K.; Ober-Blöbaum, Sina; Dellnitz, M.; Tantar, Emilia (EVOLVE - A Bridge Between Probability, Set Oriented Numerics, and Evolutionary Computation)

Variational integrators for electric circuits - Ober-Blöbaum, Sina; Tao, M.; Cheng, M.; Owhadi, H.; Marsden, J.E. (Journal of Computational Physics)

A variational approach to define robustness for parametric multiobjective optimization problems - Witting, K.; Ober-Blöbaum, Sina; Dellnitz, M. (Journal of Global Optimization)

A variational approach to multirate integration for constrained systems - Leyendecker, S.; Ober-Blöbaum, Sina (Jean-Claude Samin and Paul Fisette, editors, Multibody Dynamics)

Optimal control of a switched reluctance drive by a direct method using a discrete variational principle - Flaßkamp, K.; Ober-Blöbaum, Sina; Schneider, T.; Böcker, J. (52nd IEEE International Conference on Decision and Control)

A multiobjective optimization approach for optimal control problems of mechanical systems with uncertainties - Ober-Blöbaum, Sina; Seifried, A. (European Control Conference)

Discretized switching time optimization problems - Flaßkamp, K.; Murphey, T.; Ober-Blöbaum, Sina (European Control Conference)

Optimale Steuerungsstrategien für selbstoptimierende mechatronische Systeme mit mehreren Zielkriterien - Flaßkamp, K.; Ober-Blöbaum, Sina (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Sichere Konvoibildung mit Hilfe optimaler Bremsprofile - Heinzemann, C.; Krüger, M.; Schäfer, W.; Trächtler, A.; Flaßkamp, K.; Steenken, D.; Ober-Blöbaum, Sina; Wehrheim, H. (9. Paderborner Workshop Entwurf mechatronischer Systeme)

Discretetime model of an IPMSM based on variational integrators - Specht, A.; Ober-Blöbaum, Sina; Wallscheid, O.; Romaus, C.; Böcker, J. (IEEE International Electric Machines & Drives Conference (IEMDC))

A numerical approach to multiobjective optimal control of multibody dynamics - Ringkamp, M.; Ober-Blöbaum, Sina; Leyendecker, S. (ECCOMAS Thematic Conference on Multibody Dynamics)

Asynchronous variational Lie group integration for geometrically exact beam dynamics - Demoures, F.; Gay-Balmaz, F.; Leitz, T.; Leyendecker, S.; Ober-Blöbaum, Sina; Ratiu, T.S. (Proceedings of Applied Mathematics and Mechanics)

Multiobjective optimal control of a four-body kinematic chain - Ringkamp, M.; Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Computing time investigations of variational multirate systems - Gail, T.; Leyendecker, S.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Optimization for discretized switched systems - Flaßkamp, K.; Murphey, T.; Ober-Blöbaum, Sina (Proceedings of Applied Mathematics and Mechanics)

Erfolgreiche Berufsorientierung für Jugendliche. Forschungsergebnisse und Handlungsempfehlungen für die schulische und sozialpädagogische Praxis - Bührmann, Thorsten; Wiethoff, Christoph

Planung von Cross-Industry-Innovationen – Methodik für einen branchenübergreifenden Lösungstransfer} - Amshoff, Benjamin; Echterhoff, Niklas; Gausemeier, Jürgen; Grote, Anne-Christin